2016
DOI: 10.1080/15384047.2016.1250987
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of B-RafV600E melanoma cell survival by targeting mitochondria using triphenyl-phosphonium-conjugated nitroxide or ubiquinone

Abstract: Most BRAF-mutated melanomas initially responsive to the FDA-approved inhibitors preferentially targeting B-Raf mutated in Val600 residue eventually relapse, requiring additional therapeutic modalities. Recent studies report the significance of metabolic reprograming in mitochondria for maintenance of BRAF-mutated melanomas and for development of their drug resistance to B-Raf inhibitors, providing a rationale for targeting mitochondria as a potential therapeutic strategy for melanoma. We therefore determined w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 33 publications
0
19
0
1
Order By: Relevance
“…-Suppression of BRAF (V600E) using different types of compounds that induce mitochondria reprograming has already shown considerable progress. In a unique recent approach triphenylo-phosphoniumconjugated nitroxide or ubiquinine was used to produce mitochondrial-membrane depolarization and subsequent oxidative stress (Hong et al, 2017). The results showed that PLX4032 resistant melanoma cells become sensitive in vitro and as well in murine SK-MEL28 xenografts without serious effects.…”
Section: New Anti-melanoma Therapeutic Approaches Based On Redox-relamentioning
confidence: 99%
“…-Suppression of BRAF (V600E) using different types of compounds that induce mitochondria reprograming has already shown considerable progress. In a unique recent approach triphenylo-phosphoniumconjugated nitroxide or ubiquinine was used to produce mitochondrial-membrane depolarization and subsequent oxidative stress (Hong et al, 2017). The results showed that PLX4032 resistant melanoma cells become sensitive in vitro and as well in murine SK-MEL28 xenografts without serious effects.…”
Section: New Anti-melanoma Therapeutic Approaches Based On Redox-relamentioning
confidence: 99%
“…The studies conducted on the human melanoma cell lines (SK-MEL28, A375 and RPMI-7951) showed that Mito-CP effectively induced oxidative stress and in consequence depolarization of the mitochondrial membrane and apoptosis. Additionally, these tests exhibited a greater efficacy of nitroxide in comparison to a proto-oncogene BRAF inhibitor, Vemurafenib (PLX4032) [ 82 ].…”
Section: Nitroxides In Cancer Therapymentioning
confidence: 99%
“…HIFs, which are degraded upon exposure to ROS, can be stabilized in hypoxic conditions and promote mitophagy . Autophagy‐mediated HIF2α degradation was shown to suppress renal tumorigenesis . The significance of metabolic reprogramming in mitochondria for maintenance of BRAF‐mutated melanomas and for development of their drug resistance to B‐Raf inhibitors has been reported …”
Section: Mdf In Pathological Conditionsmentioning
confidence: 99%
“…72 Autophagy-mediated HIF2 degradation was shown to suppress renal tumorigenesis. 76 The significance of metabolic reprogramming in mitochondria for maintenance of BRAF-mutated melanomas and for development of their drug resistance to B-Raf inhibitors has been reported. 77 MDF has strongly been linked to attenuation of apoptosis, and hence, increased cancer growth and progression.…”
Section: Mechanisms Contributing To Mdf In Cancer: Apoptosis and Automentioning
confidence: 99%